Cash : the autobiography - Cash, Johnny (San Francisco, CA Harper, 1997)
Autobiography reflecting on the country musician's childhood on an Arkansas cotton farm, the early years at Sun Records, singing at the Grand Ole Opry, life on the road, years of addiction to amphetamines and pain pills, and his deep devotion to his wife, June, and their family
A Recording Overview, A Johnny Cash Discography.
Keywords: Cash, Johnny -- Biography; Country musicians -- Biography -- United States